Poor 10-year survivorship of hip resurfacing arthroplasty: 5,098 replacements from the Finnish Arthroplasty Register - Seppanen M; Karvonen M; Virolainen P; Remes V; Pulkkinen P; Eskelinen A; Liukas A; Makela KT (TAYLOR & FRANCIS LTD, 2022)
Background and purpose In a previous registry report, short-term implant survival of hip resurfacing arthroplasty (HRA) in Finland was found to be comparable to that of total hip arthroplasty (THA). Since then, it has become evident that adverse reactions to metal debris (ARMDs) may also be associated with HRA, not only with large-diameter head metal-on-metal THA. The aim of the study was to assess medium- to long-term survivorship of HRA based on the Finnish Arthroplasty Register (FAR).Patients and methods 5,068 HRAs performed during the period 2001-2013 in Finland were included. Kaplan-Meier survival analysis was used to calculate survival probabilities and their 95% confidence intervals (CIs). Cox multiple regression, with adjustment for age, sex, diagnosis, femoral head size, and hospital volume was used to analyze implant survival of HRA devices with revision for any reason as endpoint. The reference group consisted of 6,485 uncemented Vision/Bimetric and ABG II THAs performed in Finland over the same time period.Results The 8-year survival, with any revision as an endpoint, was 93% (CI: 92-94) for Birmingham Hip Resurfacing (BHR), 86% (CI: 78-94) for Corin, 91% (CI: 89-94) for ReCap, 92% (CI: 89-96) for Durom, and was 72% (CI: 69-76) for the Articular Surface Replacement (ASR). The 10-year survival, with any revision as an endpoint, for reference THAs was 92% (CI: 91-92) and for all HRAs it was 86% (CI: 84-87%). Female HRA patients had about twice the revision risk of male patients. ASR had an inferior outcome: the revision risk was 4-fold higher than for BHR, the reference implant.Interpretation The 10-year implant survival of HRAs is 86% in Finland. According to new recommendations from NICE (The National Institute for Health and Care Excellence), an HRA/THA should have a revision rate of 5% or less at 10 years. None of the HRAs studied achieved this goal.